Analysis of Potato Commodity Competitiveness Development Strategy at Sembalun Village in East Lombok Regency of Nusa Tenggara Barat - Rahayu, Intan Dwi; Sukardi, L. (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research was to analyze the effort to improved competitiveness of potato commodities. This research employed a descriptive method and used data collection techniques of survey and interview. The data analyses being used were descriptive analysis and SWOT, and analytic hierarchy process (AHP). The result showed that there were five chain structures of potato commodity supply. Internal and external factor each has eight criteria which were made to alternative strategies. AHP suggests that strategies of internal factor are the development of facilities and infrastructure for potato commodity, increasing potato seeds availability, broadening market information, optimizing the utilization of potential cultivation area in Sembalun, improving and exploiting farmers’ potato cultivation experience, improving potato quality, utilizing available workers in potato post-harvest handling process, and reducing overproduction. Furthermore, the strategies of external factor are sharpening potato farmer’s skill, following the competition level, improving production opportunities in dry season, reducing risk level of extreme climate, practicing and making use of available government policy, improving the production to meet consumer demand, reducing pests and diseases and minimizing the fluctuations in potato price.